Konsep Dasar Pengembangan Struktur Ruang Kota/Permukiman di Kalimantan Tengah (Balajar dari Kota Palangkaraya) - . Wijanarka (The Institute for Research and Community Services, Institut Teknologi Bandung, 2000)
The background of this paper is the worries that city development will have impact on the disappearance of traditional pattern that is the basic pattern of development of most cities in Central Kalimantan. With these worries, the goal of this paper is to define city development concept for ci fies in Central Kalimantan. Three basic concepts of development were defined: 1) Fully traditional concept of development, 2). Transitional concept of development from traditional to modern development, and 3). Mix of traditional and modern development.